Biomarkers and Predictors of Adverse Cardiovascular Events in Different Stages of Chronic Kidney Disease. Issue 3 (14th September 2022) - Stopic, Bojan; Medic-Brkic, Branislava; Savic-Vujovic, Katarina; Davidovic, Zeljko; Todorovic, Jovana; Dimkovic, Nada
Chronic kidney disease (CKD) is an important factor that contributes to the increase of all-cause morbidity and mortality in the group of non-communicable diseases, and it is also recognized as a strong and independent risk factor that contributes to cardiovascular disease (CVD). CVDs are a consequence of the action of a large number of risk factors among which are traditional and non-traditional. These risk factors have been the subject of a large number of studies which partially explained the unfavorable cardiovascular (CV) outcome of CKD patients. Therefore, valid studies about clinical and biohumoral predictors are of particular importance, especially in the early stages of renal disease, that is, in patients with creatinine clearance below 60 ml/min/1.73 m 2 when preventive measures are most effective. Among potential predictors of adverse CV outcome are biomarkers of inflammation (Interleukin-18—IL-18), oxidative stress (ischemia-modified albumin—IMA; superoxide dismutase—SOD), acute kidney injury (kidney injury molecule - 1—KIM-1; neutrophil gelatinase–associated lipocalin—NGAL), and microribonucleic acids (specific microRNA-133a). In this review, we tried to confirm the relationship between risk factors of CKD and CVD and newer, less frequently examined biomarkers with the occurrence of incidental CV events in renal patients.